(untitled) (Studia theodisca, 2025)
Herta Müller’s work explores the role of photography, particularly passport photos, as a symbol of identity and a tool of state control. In The Passport and Traveling on One Leg, passport photos reveal the fragmentation and alienation of the characters under oppressive regimes. Through photography, Müller highlights the gap between self-perception and state-imposed identity. The photos, meant to confirm identity, instead reflect its complexity, revealing the struggle between individual freedom and external power structures.